Choline Protects the Heart from Doxorubicin-Induced Cardiotoxicity through Vagal Activation and Nrf2/HO-1 Pathway. (5th April 2022) - Guo, Fuding; Wang, Yueyi; Wang, Jun; Liu, Zhihao; Lai, Yanqiu; Zhou, Zhen; Liu, Zihan; Zhou, Yuyang; Xu, Xiao; Li, Zeyan; Wang, Meng; Yu, Fu; et al.
Abstract : Choline is a precursor of the major neurotransmitter acetylcholine and has been demonstrated beneficial in diverse models of cardiovascular disease. Here, we sought to verify that choline protects the heart from DOX-induced cardiotoxicity and the underlying mechanisms. The results showed that DOX treatment decreased left ventricular ejection fraction and fractional shortening and increased serum cardiac markers and myocardial fibrosis, which were alleviated by cotreatment with choline. DOX-induced cardiotoxicity was accompanied by increases in oxidative stress, inflammation, and apoptosis, which were rectified by choline cotreatment. Levels of nuclear factor erythroid 2-related factor 2 (Nrf2) and heme-oxygenase-1 (HO-1), which are antioxidant markers, were lowered by DOX and upregulated by choline. Moreover, DOX significantly decreased serum acetylcholine levels and the high-frequency component of heart rate variability and increased serum norepinephrine levels and the low-frequency component; these effects were rescued by choline administration. Interestingly, the protective effects of choline could be partially reversed by administration of the muscarinic receptor antagonist atropine. This suggests that choline might be a promising adjunct therapeutic agent to alleviate DOX-induced cardiotoxicity.